Simultaneous atomic-level visualization and high precision photocurrent measurements on photoelectric devices by in situ TEM. Issue 2 (3rd January 2018) - Dong, Hui; Xu, Tao; Sun, Ziqi; Zhang, Qiubo; Wu, Xing; He, Longbing; Xu, Feng; Sun, Litao
Abstract : A photoelectric system is capable of simultaneous atomic-level visualization and pico-ampere-precision. Abstract : Herein, a novel in situ transmission electron microscopy (TEM) method that allows high-resolution imaging and spectroscopy of nanomaterials under simultaneous application of different stimuli, such as light excitation, has been reported to directly explore structure–activity relationships targeted towards device optimization. However, the experimental development of a photoelectric system capable of combining atomic-level visualization with simultaneous electrical current measurement with picoampere-precision still remains a great challenge due to light-induced drift while imaging and noise in the electrical components due to background current. Herein, we report a novel photoelectric TEM holder integrating an LED light source covering the whole visible range, a shielding system to avoid current noise, and a picoammeter, which enables stable TEM imaging at the atomic scale while measuring very small photocurrents (pico ampere range). Using this high-precision photoelectric holder, we measured photocurrents of the order of pico amperes for the first time from a prototype quantum dot solar cell assembled inside a TEM and obtained atomic-level imaging of the photo anode under light exposure. This study paves the way towards obtaining mechanistic insights into the operation of photovoltaic devices by providing direct information on the structure–activity relationships that can be used in device optimization.